2006
DOI: 10.1577/t04-204.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Introduced Summer Steelhead Hatchery Stock on the Productivity of a Wild Winter Steelhead Population

Abstract: Abstract.-We investigated the effect of a hatchery program for summer steelhead Oncorhynchus mykiss on the productivity of a wild winter steelhead population in the Clackamas River, Oregon. We used a suite of Ricker and Beverton-Holt stock-recruitment models that incorporated species interaction variables to demonstrate that when high numbers of hatchery summer steelhead adults were present the production of wild winter steelhead smolts and adults was significantly decreased. We found that large releases of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 28 publications
1
36
3
1
Order By: Relevance
“…1). For Oregon, we used Oregon Department of Fish and Wildlife unpublished data (J. Spangler, personal communication) and Kostow and Zhou (2006) to estimate SARs for five (one wild and four hatchery) populations. For BC, we used BC Ministry of Forests, Lands, and Natural Resource Operations unpublished data (T. Davies, personal communication) to estimate SARs for one wild population.…”
Section: Sar Datamentioning
confidence: 99%
“…1). For Oregon, we used Oregon Department of Fish and Wildlife unpublished data (J. Spangler, personal communication) and Kostow and Zhou (2006) to estimate SARs for five (one wild and four hatchery) populations. For BC, we used BC Ministry of Forests, Lands, and Natural Resource Operations unpublished data (T. Davies, personal communication) to estimate SARs for one wild population.…”
Section: Sar Datamentioning
confidence: 99%
“…The introduction of hatcheryproduced fish can be a major cause of ecological perturbation in salmon and steelhead populations (Fresh 1997). Recent research has demonstrated that the ecological effects of hatchery programs may significantly reduce wild population productivity and abundance even where genetic risks do not occur Kostow and Zhou 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Учёные подчёркивают, что значи-тельная доля заводских рыб может заметно снизить численность и продуктивность диких популяций (Reisenbichler, Rubin, 1999;Ford, 2002;Ford et аl., 2006;Araki et аl., 2008;Kostow, 2009Kostow, , 2012Zaporozhets, Zaporozhets, 2012;Hayes et аl., 2013). По мнению Костов и Жоу (Kostow, Zhou, 2006), искусственное воспроизводство оказывает менее заметное влияние на естественные популяции лососей, когда доля заводских рыб не превышает 10-12 %.…”
Section: результаты и их обсуждениеunclassified